Clinical decision-making in the assessment and management of sedation in intensive care - Ramelet, Anne-Sylvie; Eusebio, M. (2009)
This research review aimed to critically appraise the study by Aitken et al. on the clinical decision-making process that ICU nurses use when assessing and managing sedation in critically ill patients. © 2009 Australian College of Critical Care Nurses Ltd.